1962
DOI: 10.1073/pnas.48.10.1868
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic Heterogeneity of Glucose-6-Phosphate Dehydrogen Ase and Its Relationship to Enzyme Deficiency in Man

Abstract: 33 Kurland and Maal0e3E postulate that the effect is due to a constant small turnover of proteins. In the presence of chloramphenicol the degradation would be unimpaired, but since the rebuilding of proteins is stopped, the amino acid pool would be replenished. For this idea experimental evidence is given; indeed they showed that in bacteria which had been starved for the required amino acid, the RNA synthesis initiated by chloramphenicol recovers later than in that case where both an amino acid and chloramphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
4

Year Published

1964
1964
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(35 citation statements)
references
References 9 publications
1
30
0
4
Order By: Relevance
“…Kirkman and associates have reported patients with CNSHA with G-6-PD electrophoretic mobility similar to normal Caucasians, type B ( 18,19). The patient designated "Eysson" by Boyer and colleagues (16) showed a slower mobility than type B. Obviously, comparative studies of these more unusual deficient patients should be carried out.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kirkman and associates have reported patients with CNSHA with G-6-PD electrophoretic mobility similar to normal Caucasians, type B ( 18,19). The patient designated "Eysson" by Boyer and colleagues (16) showed a slower mobility than type B. Obviously, comparative studies of these more unusual deficient patients should be carried out.…”
Section: Resultsmentioning
confidence: 99%
“…Characterization of the erythrocyte G-6-PD from normal and drug-sensitive male Negro patients has been reported (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). The enzyme from the drug-sensitive Negro male was indistinguishable from that of normal Negro males with respect to substrate and inhibitor affinity, pH optimum, and general stability (7).…”
mentioning
confidence: 99%
“…Thus, it was initially assumed that G6PD deficiency was a single disorder, but the studies of Marks and Gross 43 showed that G6PD deficiency in Mediterranean peoples was much more severe than among African-Americans. With the development of electrophoretic methods for measuring the mobility of the enzyme on starch gel 44 and for studying the kinetic properties of the residual enzyme, 45 much greater heterogeneity became apparent. These methods were standardized by an expert committee convened by the World Health Organization (WHO), and these standard methods were used by most investigators.…”
Section: All G6pd Deficiency Is Not the Samementioning
confidence: 99%
“…Of 55 patients sequenced, 29 carried at least one G6PD A− allele (i.e., containing the nonpathogenic A376G and pathogenic G202A substitutions). The G6PD A+ allele (A376G alone), exhibiting normal enzymatic activity, 30 was the only other variant detected. All biochemically deficient males were hemizygous for the A− variant; all biochemically deficient females were heterozygotes, except for one homozygous deficient female, whose enzyme level resembled that of male hemizygotes.…”
Section: Resultsmentioning
confidence: 97%